State-dependent function of neocortical chandelier cells. - Woodruff, A; McGarry, L; Vogels, T; Inan, M; Anderson, SA; Yuste, R (2011)
Chandelier (axoaxonic) cells (ChCs) are a distinct group of GABAergic interneurons that innervate the axon initial segments of pyramidal cells. However, their circuit role and the function of their clearly defined anatomical specificity remain unclear. Recent work has demonstrated that chandelier cells can produce depolarizing GABAergic PSPs, occasionally driving postsynaptic targets to spike. On the other hand, other work suggests that ChCs are hyperpolarizing and may have an inhibitory role. These disparate functional effects may reflect heterogeneity among ChCs. Here, using brain slices from transgenic mouse strains, we first demonstrate that, across different neocortical areas and genetic backgrounds, upper Layer 2/3 ChCs belong to a single electrophysiologically and morphologically defined population, extensively sampling Layer 1 inputs with asymmetric dendrites. Consistent with being a single cell type, we find electrical coupling between ChCs. We then investigate the effect of chandelier cell activation on pyramidal neuron spiking in several conditions, ranging from the resting membrane potential to stimuli designed to approximate in vivo membrane potential dynamics. We find that under quiescent conditions, chandelier cells are capable of both promoting and inhibiting spike generation, depending on the postsynaptic membrane potential. However, during in vivo-like membrane potential fluctuations, the dominant postsynaptic effect was a strong inhibition. Thus, neocortical chandelier cells, even from within a homogeneous population, appear to play a dual role in the circuit, helping to activate quiescent pyramidal neurons, while at the same time inhibiting active ones.